Microeconometrics : methods and applications - Cameron, Adrian Colin; Trivedi, P. K. (Cambridge : Cambridge University Press, 2005)
This book provides the most comprehensive treatment to date of microeconometrics, the analysis of individual-level data on the economic behavior of individuals or firms using regression methods for cross section and panel data. The book is oriented to the practitioner. A basic understanding of the linear regression model with matrix algebra is assumed. The text can be used for a microeconometrics course, typically a second-year economics PhD course; for data-oriented applied microeconometrics field courses; and as a reference work for graduate students and applied researchers who wish to fill in gaps in their toolkit. Distinguishing features of the book include emphasis on nonlinear models and robust inference, simulation-based estimation, and problems of complex survey data. The book makes frequent use of numerical examples based on generated data to illustrate the key models and methods. More substantially, it systematically integrates into the text empirical illustrations based on seven large and exceptionally rich data sets.
Distinctive Aspects of Microeconometrics -- Book Outline -- Software -- Notation and Conventions -- Causal and Noncausal Models -- Structural Models -- Exogeneity -- Linear Simultaneous Equations Model -- Identification Concepts -- Single-Equation Models -- Potential Outcome Model -- Causal Modeling and Estimation Strategies -- Microeconomic Data Structures -- Observational Data -- Data from Social Experiments -- Data from Natural Experiments -- Core Methods -- Linear Models -- Regressions and Loss Functions -- Example: Returns to Schooling -- Ordinary Least Squares -- Weighted Least Squares -- Median and Quantile Regression -- Model Misspecification -- Instrumental Variables -- Instrumental Variables in Practice -- Maximum Likelihood and Nonlinear Least-Squares Estimation -- Overview of Nonlinear Estimators -- Extremum Estimators -- Estimating Equations -- Statistical Inference -- Maximum Likelihood -- Quasi-Maximum Likelihood -- Nonlinear Least Squares -- Example: ML and NLS Estimation -- Generalized Method of Moments and Systems Estimation -- Generalized Method of Moments -- Linear Instrumental Variables -- Nonlinear Instrumental Variables -- Sequential Two-Step m-Estimation -- Minimum Distance Estimation -- Empirical Likelihood -- Linear Systems of Equations -- Nonlinear Sets of Equations -- Hypothesis Tests -- Wald Test -- Likelihood-Based Tests -- Example: Likelihood-Based Hypothesis Tests -- Tests in Non-ML Settings -- Power and Size of Tests -- Monte Carlo Studies -- Bootstrap Example.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Microeconomics -- Econometric models